Implementation of Procurement and Utilization Policies for School Facilities and Infrastructure Based on Students’ Needs at TKN 1 Plus Banyuasin III - Ican Setiawan; Nila Kesumawati; Alhadi Yan Putra (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aimed to analyze the implementation of procurement and utilization policies for school facilities and infrastructure based on students' needs at TKN 1 Plus Banyuasin III. A qualitative descriptive approach was employed involving the principal, teachers, and school committee members selected through purposive sampling because of their direct involvement in school facilities management. Data were collected through interviews, observations, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that the implementation of school facilities and infrastructure policies has generally been carried out systematically through participatory planning, procurement, utilization, maintenance, and periodic evaluation. Educational facilities have supported active learning and students' cognitive, social, and motor development. Nevertheless, limited budgets, inadequate facilities, and insufficient human resource competencies remain significant barriers. This study contributes to educational management by emphasizing that effective school facilities management depends not only on resource availability but also on participatory decision-making, leadership commitment, and needs-based policy implementation in early childhood education institutions.